Soll und Haben : Dauerleihgaben und Neuerwerbungen 1990-1993. - Zweite, Armin; Kunstsammlung Nordrhein-Westfalen, Düsseldorf (Düsseldorf : Kunstsammlung Nordrhein-Westfalen, 1993)
Andre, Carl ; Beuys, Joseph ; Caro, Anthony ; Chamberlain, John ; Ernst, Max ; Gerz, Jochen ; Judd, Donald ; Kirkeby, Per ; Knoebel, Imi ; LeWitt, Sol ; Lüpertz, Markus ; Newman, Barnett ; Nitsch, Hermann ; Rainer, Arnulf ; Rauschenberg, Robert ; Richter, Gerhard ; Scully, Sean ; Serra, Richard ; Turrell, James
boek